Arquivo da Comissão Pastoral da Terra (Belém): desafios e perspectivas no tratamento documental - AVIZ, Emanuelle França de (2023)
The objective of this work is to present the experience developed as a scientific initiation scholarship holder with the archive of the Pastoral Land Commission (CPT) of Belém, an institution that throughout its trajectory has produced a significant collection recording peasant struggles for land. The methodology used consisted of bibliographical and documental research and a case study through which a historicalarchival analysis of the formation, organization and uses of the CPT archive was carried out with the purpose of elaborating research instruments for systematization, dissemination and preservation of its collection. As a result of this work, it was possible to identify the challenges related to the treatment of documents and contribute to the diagnosis and rearrangement of documents related to the issue of slave labor. It is concluded that the CPT archive constitutes an important documentary heritage for academic research and preservation of the memory of peasant social movements in the Amazon. For this, it is fundamental to treat this documentation in order to promote a better organization through archival techniques, thus promoting the preservation and dissemination of these documents to society.